THE GREAT CRISIS OF NEOLIBERAL CAPITALISM (Andamios, Revista de Investigación Social, 2010)
The aim of this paper is to test an explanation for the crisis in contemporary capitalism and unveil new ways to understand the way in which uneven development occurs. The crisis in neoliberal capitalism represents the decline of a project that pretended or intended to restructure and expand neoliberal capitalism. Led by collective imperialism in an epoch, which places humanity at a corresponding crossroads: capital or life. Anticipating capital as the possible answer, this paper postulates the need to generate alternatives to postneoliberal or post-capitalist development, (which still contributes to the overexploitation, environmental devastation and centralized accumulation), in order to create better working and living conditions for most of the population and thus, into the center of the need to guarantee the reproduction of human life on the planet.
Keywords: Crisis; capitalism; uneven development; center-periphery; neoliberalism